Faktor Risiko Kejadian Stunting pada Bayi 6-12 Bulan di Wilayah Kerja Puskesmas Air Dingin Kota Padang - Sevilla Ukhtil Huvaid; Erni Maywita; Riska Delvi Kurnia (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
According to the monitoring of nutritional status for toddlers in 2017, as many as 30.6% of toddlers in West Sumatra experienced stunting, which is a short combination (21.3%) and very short (9.3%) with an incidence in Padang city of 22 6%. DKK data, 2017 the prevalence of stunting in Padang City is 20.04% of the 22 Puskesmas in Padang City found the highest prevalence of stunting in Puskesmas Air Dingin is 57.14%. The purpose of this study was to determine the risk factors for stunting in infants aged 6-12 month in the working area of the Padang Air Cold Health Center in 2019. This type of research is an analytic survey with case control design. The time of the study was May-August 2019. The population was cases of mothers having infants aged 6-12 months who experienced stunting and control in normal infants in the working area of the Padang Air Cold Health Center with a ratio of 1: 1 ie 30 cases, 30 controls then the number of 60 study samples using a questionnaire. Cases and controls where the age and sex variables are maching variables. Univariate data analysis is displayed with a frequency distribution table and bivariate analysis using the chi-square test with significance, α = 0.05. The results showed 56.7% of babies had low birth weight, 55.0% of parents had good parenting, 50% of babies had a stunting event, there was a significant relationship between Low Birth Weight with stunting with p = 0.001, OR = 8 and there is a significant relationship between parenting with the incidence of stunting in infants 6-12 months in the Cold Water Puskesmas Work Area in Padang City in 2019 with p = 0.038 and OR = 3.5. It is expected that there is a proven relationship between Low Birth Weight and parental care with the occurrence of stunting in infants aged 6-12 months and to health workers at the Padang Air Cold Health Center in order to provide education about stunting and explain good parenting to prevent stunting in infants.